Analisa Semiotika Roland Barthes: Representasi Citra Belle Epoque pada Iklan Parfum Chanel No 5 Tahun 1960 - Jayanti, Ghia Tri (CandraRupa : Journal of Art, Design, and Media, 2025)
Chanel, a legendary fashion brand from France, is present as a new revolution in the social order of society after World War I. The revolution of image and freedom began to grow bigger after Coco Chanel, the founder of Chanel, offered a new concept, a concept of women's freedom in expressing themselves. The concept of freedom from the patriarchal system that displays the image of feminism, independence, and the process of French women's freedom offered in the Chanel No. 5 perfume advertisement in 1960. This study identifies and analyzes the term Belle Epoque, in French this term refers to the position of women as a balancing role in modern French society. The image of Belle Epoque is an image of a human being who can be graceful, feminine and modest in freedom. This Belle Epoque concept is presented by Chanel in an advertisement that offers an image of equality of glamorous and luxurious French women. This Chanel advertisement becomes an ideological discourse that is analyzed using Rolland Bartes' semiotic approach. This method is an act of communication (semiotics of communication) with principles that refer to the vocabulary of signs, codes, and rules and have been determined by the language system (semiotics of significance) and the level of signs or elements of sociology and produce meaning in language (linguistics) behind the meaning, 'literal' (denotation) of words and can have connotations or further meanings in semiotics. The denotation and connotation found in this advertisement explain the relationship between the signifier and the signified used to produce the ideological process in the image of the Chanel No. 5 Perfume Advertisement in 1960.